PENGARUH PERSEPSI GENERASI Y TERHADAP PILIHAN KARIR PADA MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS AHMAD DAHLAN - Adeliyanti, Adeliyanti; Khoirunnisa, Rikha Muftia (Jurnal Fokus Manajemen Bisnis, 2019)
This study aims at finding out the influence of the perception of generation Y (consideration of job market, career motivation, family influence, social value of job, and career lifestyle) on career choice in students of Management Study Program of Ahmad Dahlah University. The population of the study was students of Management Study Program of Ahmad Dahlan University of class 2015. The sample collecting technique used was purposive sampling, with a sample critrion of those who took thesis subject with a total og 212 students. The data analysis used in the study was multiple linear regression analysis. The findings of the study show that the career motivation and socual value of the job significantly influenced career choice in students of Management Study Program of Ahmad Dahlan Unversity, while the consideration of job market, family influence and career lifestyle did not significantly influence career choice in students of Management Study Program of Ahmad Dahlan Unversity. Futhermore, through F test, is showed that the consideration of job market, career motivation, family influence the social value of job and career lifestyle simultaneously significantly influenced career choice in students of Management Study Program of Ahmad Dahlan University. The R square calue obtained was 0,772. This, it can be interpreted that the influence contribution of the independent variables (consideration of job market (X1), career motivation (X2), family influence (X3), social value of job (X4) and career lifestyle (X5) on the dependent variable career choice (Y) was 77,2%, while the other 22,8% can be explained by other variables that were not observed in this study.